Rigidity and flexibility characteristics of DD[E/D]-transposases Mos1 and Sleeping Beauty. - Singer, Christopher M. (Proteins, 2019)
DD[E/D]-transposases catalyze the multistep reaction of cut-and-paste DNA transposition. Structurally, several DD[E/D]-transposases have been characterized, revealing a multi-domain structure with the catalytic domain possessing the RNase H-like structural motif that brings three catalytic residues (D, D, and E or D) into close proximity for the catalysis. However, the dynamic behavior of DD[E/D]-transposases during transposition remains poorly understood. Here, we analyze the rigidity and flexibility characteristics of two representative DD[E/D]-transposases Mos1 and Sleeping Beauty (SB) using the minimal Distance Constraint Model (mDCM). We find that the catalytic domain of both transposases is globally rigid, with the notable exception of the clamp loop being flexible in the DNA-unbound form. Within this globally rigid structure, the central β-sheet of the RNase H-like motif is much less rigid in comparison to its surrounding α-helices, forming a cage-like structure. The comparison of the original SB transposase to its hyperactive version SB100X reveals the region where the change in flexibility/rigidity correlates with increased activity. This region is found to be within the RNase H-like structural motif, comprising the loop leading from beta-strand B3 to helix H1, helices H1 and H2, which are located on the same side of the central beta-sheet, and the loop between helix H3 and beta-strand B5. We further identify the RKEN214-217DAVQ mutations of the set of hyperactive mutations within the catalytic domain of SB transposase to be the driving factor that induces change in residue-pair rigidity correlations within SB transposase. Given that a signature RNase H-like structural motif is found in DD[E/D]-transposases and, more broadly, in a large superfamily of polynucleotidyl transferases, our results are relevant to these proteins as well.